Current Status of Metabolic Compliance and Risk of Cardiovascular Disease in Patients with Type 2 Diabetes in the Zhuang Population in China - Danqing Xu; Xia Dai; Qiong Yang; Xueying Li; Ying Xiao; Qiuhong Huang; null Qingqing Lou (International Journal of Endocrinology)
Introduction. This study aimed to investigate the blood glucose, blood pressure, and blood lipid status in Zhuang patients with T2DM and to analyze the correlation between compliance with metabolic monitoring and cardiovascular risk factors. Methods. A total of 1975 Zhuang patients with T2DM were evaluated in four Class III Grade A hospitals in three prefecture-level cities in the Guangxi Zhuang Autonomous Region between January and August 2022. Laboratory indicators, lifestyle, and demographic characteristics were collected. Results. The compliance rates for blood glucose, blood pressure, and blood lipids were 26.08%, 45.77%, and 30.58%, respectively, and only 5.06% of the patients reached the standard in all three indices. The compliance rates for blood glucose, blood pressure, and blood lipids in the CVD group were 32.92%, 21.74%, and 9.94%, respectively. In the CVD group, the usage rates of hypoglycemic, antihypertensive, and lipid-lowering drugs were 77.54%, 3.17%, and 4.11%, respectively. Binary logistic regression analysis showed that older age (OR = 1.033, 95% CI [1.016, 1.050]), female (OR = 0.402, 95% CI [0.260, 0.621]), smoke (OR = 1.994, 95% CI [1.361, 2.922]), blood pressure noncompliance + use of antihypertensive drugs (OR = 0.348, 95% CI [0.230, 0.527]), and blood lipid noncompliance + use of lipid-lowering drugs (OR = 0.244, 95% CI [0.142, 0.417]) were risk factors for CVDs, and moderate-intensity exercise (OR = 0.439, 95% CI [0.300,0.640]) was protective against CVD. Conclusions. Older age, female, smoke, blood lipid levels, and blood pressure noncompliance were risk factors for CVD while moderate-intensity exercise was observed to be protective.